From pity to productivity: the case of social cash transfers in Mozambique - Le, Teresa Nguyen (My University, 2016)
Social cash transfer programmes on the African continent have more than doubled in the last decade, and this signifies a transformation in the perception of social cash transfers as ‘pity handouts’ to how they are seen today, as ‘productive investments’ in human capabilities. Southern Africa has been a pioneer in social protection growth in the last twenty years, but often accounts of these histories focus on pension schemes in places such as South Africa, Namibia, Botswana, and Lesotho. There is little incorporation of Mozambique’s social protection history, and most histories do not detail that Mozambique ranks fourth chronologically, in introduction of cash transfer programmes in Sub-Saharan Africa. This research puts forth that the Mozambican case of an early adoption of cash transfers in 1990 is a positive and unique example of a state’s active role in social protection despite neoliberal constraints. The state-led adoption of cash transfers in response to rising inequality and economic instability is unexpected at a time when these programmes were unpopular development interventions and when the state was supposedly rolled-back and confined because neoliberalism and the civil war. Tracing the history of Mozambican social cash transfers in the last 25 years illustrates two consistencies of the Mozambican government: 1. A supportive political position towards state involvement in welfare programmes, despite the government’s own political and development sector transformation from Marxist-Leninist orientation to welcoming of privatization; and 2. State financial and political support of social protection throughout a period when cash transfers in Sub-Saharan Africa went from unpopular hand-out interventions during crises, to lobbying for permanent social protection as a mechanism to address chronic poverty.
Submitted in partial fulfilment for the requirements for Masters of Arts in Development Studies by coursework and research report In the Graduate School of Social Sciences, Faculty of Humanities, University of the Witwatersrand, 2016
Keywords: Transfer payments--Mozambique; Economic assistance, Domestic--Mozambique; Poverty--Government policy--Mozambique; Poor--Government policy--Mozambique